Early Parenteral Nutrition (PN) As A Mortality Risk Factor in COVID-19 Patients at the Intensive Care Unit (ICU) of RSUP Dr. Kariadi - Putu Prayoga Ratha; Niken Puruhita; Aryu Candra; Siti Fatimah Muis; Enny Probosari (Warmadewa University, 2025)
Mortality in COVID-19 patients in the ICU is reported to be higher than non-ICU. Early parenteral nutrition is avoided considering the complications, but COVID-19 patients in the ICU require parenteral nutrition because enteral intake is inadequate or contraindicated. This study aims to identify early parenteral nutrition and other risk factors that cause mortality of COVID-19 patients in the ICU of Dr. Kariadi Hospital. Observational analytic study using a retrospective cohort approach using secondary data involving COVID-19 patients treated in the ICU of RSUP dr. Kariadi in March – September 2020. The sampling technique used total sampling with the following criteria: inclusion: confirmed COVID-19, age >18 years and given PN and EN therapy or a combination thereof. Statistical analysis using Chi Square test and Logistic Regression. Total of 188 subjects met the inclusion criteria. There was no difference in the mortality of patients who were given early or late PN p:0.92 RR 0.90 (95% CI 0.43-1.84). The risk factors for mortality were the presence of comorbidities p=0.023 RR 2.13 (95% CI 1.15-3.95), use of VM p=<0.0001 RR 43.68 (95% CI 18.52 – 102.99) , energy deficit p=0.002 RR 3.09 (95% CI 1.52-5.99) and protein deficit p=0.039 RR 1.93 (95% CI 1.07-3.49). In the multivariate analysis of controlled VM usage with ARDS status p=0.022 RR 6.20 (95% CI 1.29 – 29.72) and energy deficit p=0.045 RR 2.15 (1.01 – 4.57) together -the same as a risk factor for mortality in COVID-19 patients in the ICU of Dr. Kariadi Hospital. Early PN is not a risk factor for mortality in COVID-19 patients while the use of VM is controlled by ARDS status and energy deficit together are risk factors for mortality in COVID-19 patients in the ICU of RSUP dr. Kariadi.